2019
DOI: 10.1016/j.ejca.2019.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in patients with a germline BRCA mutation and HER2-negative metastatic breast cancer receiving olaparib versus chemotherapy in the OlympiAD trial

Abstract: Background: The phase III OlympiAD study (NCT02000622) showed a statistically significant progression-free survival benefit with olaparib versus chemotherapy treatment of physician's choice (TPC) in patients with a germline BRCA mutation and human epidermal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 16 publications
2
67
0
8
Order By: Relevance
“…About EORTC QLQ-C30 symptoms and functioning subscales,the EMBRACA phase III trial showed that compared to the PCT arm,patients who treated with TALA signi cantly delayed TTD in all symptoms [25].Meanwhile,there is similar result in the OlympiAD trial,except vomiting/nausea symptom score compared with TPC arm [36].…”
Section: Discussionmentioning
confidence: 93%
“…About EORTC QLQ-C30 symptoms and functioning subscales,the EMBRACA phase III trial showed that compared to the PCT arm,patients who treated with TALA signi cantly delayed TTD in all symptoms [25].Meanwhile,there is similar result in the OlympiAD trial,except vomiting/nausea symptom score compared with TPC arm [36].…”
Section: Discussionmentioning
confidence: 93%
“…Later, other PARPi, such as nirapararib and rucaparib were approved [ 25 , 26 , 27 , 28 ]. On January 2018, based on data from OlympiAD trial (NCT02000622), FDA granted regular approval to Olpararib for the treatment of patients with deleterious or suspected deleterious gBRCAm, HER2-negative metastatic breast cancer previously treated with chemotherapy either in the neoadjuvant, adjuvant, or metastatic setting [ 9 ]. FDA also approved the BRACAnalysis CDx ® test (Myriad Genetic Laboratories, Inc., Salt Lake City, UT, USA), whose accuracy was established based on a retrospective/prospective analysis of the OlympiAD trial population.…”
Section: Brca1/2 and Other Genes Involved In Dna Repairmentioning
confidence: 99%
“…In the last years, a great effort has been spent to identify new biomarkers and relative therapies, but only few of these have proven useful in clinical trials. Beside poly ADP-ribose polymerase (PARP) inhibitors, that have successfully been incorporated in the clinical practice in the BRCA1/2 subgroup of patients [ 9 , 10 ], and checkpoint inhibitor Atezolizumab, that was recently approved as front-line therapy in the metastatic setting [ 11 ], traditional chemotherapy without biomarker guide still remains the main therapeutic options for a large part of TNBC patients [ 12 ]. In this context, the implementation of more refined “omics” assays, along with appropriately designed clinical trials, may lead to the identification of new biomarkers to select new molecularly targeted therapies in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…A higher proportion of patients in the olaparib arm showed improvement in global health status/quality of life (QoL) (33.7% vs 13.4%). Median time to QoL deterioration was not reached in patients receiving olaparib and was 15.3 months for patients receiving TPC (hazard ratio: 0.44 [95% CI, 0.25‐ 0.77]; P = .004) 17 …”
Section: Parpi In Advanced or Metastatic Breast Cancermentioning
confidence: 99%